(Diacetoxyiodo)benzene-Mediated Transition-Metal-Free Amination of C(sp3)–H Bonds Adjacent to Heteroatoms with Azoles: Synthesis of N-Alkylated Azoles - Sun, Bin; Yan, Zhiyang; Jin, Can; Su, Weike (Synlett, 2018)
A novel PhI(OAc)2-mediated cross-dehydrogenative coupling reaction of α-C(sp3)–H bonds adjacent to a hetero atom with various azoles has been developed, which provides an alternative method for constructing C–N bonds with high atom efficiency. This new protocol requires no metal catalyst and it provides ready access to a wide range of N-alkylated azole derivatives in moderate to excellent yields by using commercially available PhI(OAc)2 as the sole oxidant. Furthermore, the method is effective on a gram scale, which highlights the practicality of this transformation. The result of radical-captured experiments indicated that the transformation might involve a free-radical pathway.
Keywords: diacetoxyiodo benzene; C–H functionalization; C–N bond; azoles; metal-free; amination